2013
DOI: 10.1002/joc.3769
|View full text |Cite
|
Sign up to set email alerts
|

Future convective environments using NARCCAP

Abstract: This study examines trends in atmospheric environments conducive to the development of severe convection in the United States, as simulated by a regional model forced with output from a global climate model. Meteorological variables necessary for severe convection from current (1981–1995) and future (2041–2065) epochs were compared. Results indicate a statistically significant increase in the number of significant severe weather environments in the Northeast United States, Great Lakes, and Southeast Canada reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 17 publications
(38 reference statements)
3
36
0
Order By: Relevance
“…This behaviour has been noticed in previous studies such as Trapp et al (2009), who mention the influence of the decrease of SHR06 on the number of environments capable of developing severe weather is attenuated by the expected CAPE increase in the future. Gensini et al (2014) also verified an increase of the frequency of environments favourable for the development of severe weather. However, this study used a distinct discriminant line (CAPE × SHR06 > 20 000 m 3 s −3 ), which requires higher values of CAPE and/or SHR06.…”
Section: Environments Favourable For Severe Stormsmentioning
confidence: 60%
See 1 more Smart Citation
“…This behaviour has been noticed in previous studies such as Trapp et al (2009), who mention the influence of the decrease of SHR06 on the number of environments capable of developing severe weather is attenuated by the expected CAPE increase in the future. Gensini et al (2014) also verified an increase of the frequency of environments favourable for the development of severe weather. However, this study used a distinct discriminant line (CAPE × SHR06 > 20 000 m 3 s −3 ), which requires higher values of CAPE and/or SHR06.…”
Section: Environments Favourable For Severe Stormsmentioning
confidence: 60%
“…Gensini et al . () also verified an increase of the frequency of environments favourable for the development of severe weather. However, this study used a distinct discriminant line (CAPE × SHR06 > 20 000 m 3 s −3 ), which requires higher values of CAPE and/or SHR06.…”
Section: Resultsmentioning
confidence: 97%
“…In particular, additional efforts are needed to determine how instability and shear might change and how these changes might influence tornado activity. This is particularly warranted because some studies have suggested that increases in instability and low‐level humidity are likely to increase the likelihood of severe weather and tornadoes in the future (Trapp et al ., , ; Diffenbaugh et al ., ; Gensini et al ., ), but Tippett et al . () recently reported that shear, rather than instability, is better associated with observed increases in the number of extreme tornado outbreaks.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…While it is true that even CAPE >100 J kg −1 is regarded as a threshold designed to ensure that the environment can be characterized as being convective (Brooks et al 2003;Kunz et al 2009;Gensini et al 2014b), in the USA, however, thunderstorms appear when CAPE is mainly about 500 J kg −1 (Rasmussen and Blanchard 1998 In the study conducted for The Netherlands, Haklander and Van Delden (2003) determined a value of MUCAPE ≥168 J kg −1 as an optimal threshold for thunderstorm probability forecasting. In the few studies carried out for thunderstorm conditions in Poland, a value of CAPE >300 J kg −1 has been used most often (Malinowska 2011).…”
Section: Mucape As a Predictor For Thunderstorm Occurrencementioning
confidence: 99%